Healing-over in rat crystalline lens. - Bernardini, G (1981)
1. 42K efflux has been studied in normal and injured rat crystalline lenses to test their ability to heal over. Following injury, a sizeable, but transient, increase in fractional loss of 42K takes place. 2. The lens healing-over is Ca-dependent and cannot be accounted for by membrane resealing. This is excluded by the fact that Procion Yellow gains access to damaged fibres even 2 hr after injury (when the healing-over is completed). 3. The occlusion of the junctional channels is the basic mechanism of healing-over. This is supported by the observation that Procion Yellow does not diffuse from damaged to intact fibres and by the Ca dependency of the phenomenon.